2023
DOI: 10.1002/ptr.8088
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: Potential opportunities for natural products in cancer therapy

Anzheng Nie,
Chaozan Shen,
Zheng Zhou
et al.

Abstract: Cancer cells often exhibit defects in the execution of cell death, resulting in poor clinical outcomes for patients with many cancer types. Ferroptosis is a newly discovered form of programmed cell death characterized by intracellular iron overload and lipid peroxidation in the cell membrane. Increasing evidence suggests that ferroptosis is closely associated with a wide variety of physiological and pathological processes, particularly in cancer. Notably, various bioactive natural products have been shown to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 179 publications
0
2
0
Order By: Relevance
“…323 With the increasing research on ferroptosis, more and more natural products have been found to have ferroptosisinducing effects. 324 Although these natural products themselves have limited effects in inducing ferroptosis in tumor cells, their discovery has provided lead compounds for the development of ferroptosis inducers. For example, compound 31, synthesized by combining the core of the natural product indirubin with the active fragment of a GPX4 covalent inhibitor via a linker, effectively inhibited human colon cancer cells.…”
Section: Drug Potency Enhancementmentioning
confidence: 99%
“…323 With the increasing research on ferroptosis, more and more natural products have been found to have ferroptosisinducing effects. 324 Although these natural products themselves have limited effects in inducing ferroptosis in tumor cells, their discovery has provided lead compounds for the development of ferroptosis inducers. For example, compound 31, synthesized by combining the core of the natural product indirubin with the active fragment of a GPX4 covalent inhibitor via a linker, effectively inhibited human colon cancer cells.…”
Section: Drug Potency Enhancementmentioning
confidence: 99%
“…Natural products often play a role in adjusting cellular equilibrium, interacting with signaling pathways related to both cell death and survival, and displaying antioxidant and anti-inflammatory characteristics. The historical utilization of certain natural products in traditional medicine, coupled with clinical evidence supporting their safety and effectiveness in treating cancers, lend credibility to their potential as agents inducing ferroptosis ( Nie et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%